Interfacial phenomena during Fenton reaction on starch stabilized magnetite nanoparticles: Molecular dynamics and experimental investigations - Kuntail, J.; Pal, S.; Sinha, I. (Elsevier B.V., 2020)
A critical unresolved question in scientific literature is that whether the mechanism operating in heterogeneously catalyzed Fenton reactions is Langmuir-Hinshelwood (LH) or Eley-Rideal (ER) type. The present investigation combines experimental inputs with insights from molecular dynamics simulations to infer the mechanism on a catalyst surface. Experiments were carried out on the Fenton degradation of p-nitrophenol (PNP) over magnetite (MNPs), and starch stabilized magnetite nanoparticles (SMNPs). The degradation of PNP was quite slow in the presence of MNPs, but it was significantly faster on SMNPs. Classical molecular dynamics (MD) simulations under NPT conditions investigated the interactions between hydrogen peroxide and PNP molecules in aqueous surroundings with the central magnetite or starch stabilized magnetite cluster. MD results show that starch stabilization facilitates the approach of H2O2 molecules to the magnetite surface. The comparison of experimental and simulation results point to an ER type mechanism. The simulation methodology gives us a crucial stabilizer molecule selection criterion for the design of an efficient Fenton nanocatalyst. © 2020 Elsevier B.V.
Keywords: Interfacial phenomena; Fenton reaction; Molecular dynamics simulations; Starch stabilized magnetite nanoparticles